Social responsibility, organisational support, and identification: An approach to non-profit organisations - Justino, E.; Santos, G. (Social Work: Perceptions for a new era, 2024)
In an era where social responsibility is increasingly embedded in organisational strategy, this study scrutinises the infusion of social responsibility into the strategic underpinnings of non-profit organisations. Specifically, it aims to assess the influence of social responsibility initiatives on the organisational support and organisational identification of NGO employees to verify the impact of social responsibility initiatives on the organisational identification of NGO employees mediated by organisational support and to analyse the influence of organisational support on the organisational identification of NGO employees. Using a quantitative methodology, this study analyses the responses of 103 non-profit employees, focusing on the interplay between social responsibility, organisational support, and organisational identification. The research employs structural equation modelling to investigate these relationships, revealing a significant positive correlation between social responsibility initiatives and perceptions of organisational support. Furthermore, the findings suggest that organisational support serves as a pivotal mediator between social responsibility practices and employees' identification with their organisation. These insights offer profound implications for non-profits striving to amplify their societal impact, contributing to the broader discourse on organisational management and sustainability. A dynamic interplay wherein robust organisational support enhances employees' alignment with their organisation's social objectives, thereby reinforcing the commitment to social responsibility. These insights are helpful for non-profits seeking to strengthen their engagement with societal issues, suggesting that fostering organisational support is key to enhancing both organisational identification and social responsibility outcomes.